2019
DOI: 10.1101/767533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ISGylation drives basal breast tumour progression by promoting EGFR recycling and Akt signalling

Abstract: ISG15 is an ubiquitin-like modifier that is associated with reduced survival rates in breast cancer patients. However, the mechanism by which ISG15 achieves this remains elusive.We demonstrate that modification of Rab GDP-Dissociation Inhibitor Beta (GDI2) by ISG15 (ISGylation) alters endocytic recycling of the EGF receptor (EGFR). By regulating EGFR trafficking, ISGylation sustains Akt-signalling in vitro and in vivo. Persistent and enhanced Akt activation explains the more aggressive tumour behaviour observe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
(65 reference statements)
0
3
1
Order By: Relevance
“…In our experimental conditions, ISG15 gene silencing inhibited proliferation, but not migration or invasion; in contrast with other published work that observed a decrease of either of these tumoral characteristics in different malignancies [22,23,25,40,41]. However, this might indicate that ISG15 pro-tumoral functions are heterogeneous and depend on the cancer type.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our experimental conditions, ISG15 gene silencing inhibited proliferation, but not migration or invasion; in contrast with other published work that observed a decrease of either of these tumoral characteristics in different malignancies [22,23,25,40,41]. However, this might indicate that ISG15 pro-tumoral functions are heterogeneous and depend on the cancer type.…”
Section: Discussioncontrasting
confidence: 99%
“…ISG15 oncogenic mechanisms are also diverse, as it can act intracellularly in its free [27,28] or its conjugated form [22,25,44]; as well as extracellularly as a microenvironmental modulator [23,28,30]. More specifically, both paracrine secretion from M2 macrophages and autocrine ISG15 secretion from pancreatic tumour cells are able to induce a CSC phenotype in said cells [28,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that GOLM1 selectively interacts with EGFR and assists EGFR recycling back to the plasma membrane to drive hepatocellular carcinoma metastasis [35]. EGFR recycling is also regulated by ISGylation leading to the more aggressive tumor behaviors observed in breast cancer [47]. Besides these regulations, several ubiquitin ligases were also reported to be involved in EGFR trafficking and recycling such as CHIP and SMURF2 [48,49].…”
Section: Discussionmentioning
confidence: 99%